Persepsi Anggota Komunitas Samarinda Movie Mania Terhadap Unsur LGBT Dalam Film "Kucumbu Tubuh Indahku" - Lucy Hou Lisa; Silviana Purwanti; Nurliah (Journal Social Politica, 2021)
ABSTRACTThe purpose of this study was to express and find out the perceptions of members of the Samarinda movie mania community towards the LGBT element in the film "Kucumbu Tubuh Indahku". The research method used is descriptive qualitative using analytical techniques from Miles and Huberman which is intended to collect information about the status of a symptom, namely the state of symptoms according to what they are when the research is conducted. Data collection was done by conducting interviews and documentation. The resource persons in this study were 6 (six) people who were active members of the Samarinda movie mania community. Data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions. The results of this study concluded that the perceptions of members of the Samarinda Movie Mania community gave a positive response to this film itself. Because it raises a unique theme, which is still considered taboo by the public, especially in Indonesia. This film also introduces one of Indonesian culture, namely the Lengger Lanang Dance which is not widely known by the wider community.